Modifying the Ninoy Aquino Parks and Wildlife Center into an urban bat-friendly sanctuary through ecocentrism - Siscar, Alexis Joy T. (College of Architecture, University of the Philippines Diliman, 2019)
The main aim of the study is to explore how green spaces can be modified to cater to the needs of the existing wildlife residing in urban areas by utilizing the prinicple of ecocentrism, as well as raise awareness on the role of humans in ecological conservation and biodiversity preservation. The researcher chose to conduct the study in Quezon City, one of the country's most populated area, and selected the Ninoy Aquino Parks and Wildlife Center due to its strategic location. The subject of the study to design for was limited to urban bats, due to the three crucial ecosystem services that they provide - insect population control, seed dispersion, and food production. Data on which bat species residing in the city wee gathered; other green spaces were also pinpointed. From the data collected, the NAPWC's landscape design was modified, and an ecological framework schematics of how the other green spaces can be connected to each other was produced. All in all, the study concludes that in order to attract the target species to the NAPWC, one must integrated the necessary elements of their diet, movement, and habitat. An ecological framework schematics connecting other green spaces with each other must also be established to provide a safe passage from one habitat fragment to another.